Simulation of Multipurpose Reservoir Operation with Hedging Rules - Sasireka, K; R Neelakantan, T; Suriyanarayanan, S (International Journal of Engineering and Technology, 2018)
Reservoir operation plays an important role in the economic development of a region. The storage reservoirs are not only useful for supplying water for municipal and irrigation purpose, but also act as a protection barrier form flood, and the stored water can be used for generation of electricity power as well. To meet the objectives for which the reservoir was planned, it is vital to formulate guidelines for the operation of reservoir. This can be achieved by systematic operation of the system, and by the use of systematic and simplified rule curve for the operation of reservoir. Hedging rules are popular in drinking and irrigation water supply. Application of hedging is now gaining focus for hydropower power reservoir operation. In the present study, attempt has been made to formulate a new operating rule for multipurpose reservoir using hedging rules and the developed model was applied to a case study of Bargi reservoir in the Narmada basin in India. In order to increase the reliability of water supply for municipal, irrigation and average annual power production, the new operating rule has been developed using Standard Operation Policy (SOP) and hedging rule according to the priority of release for different purposes. The hedging rule based simulation model satisfies 97.5% of municipal water supply which is more than 8.25% of the present operational policy. The spill of the reservoir is decreased by 57 % compared to present policy. The performances of different hedging rules were compared with that of a new standard operating policies and the superiority of the hedging rules are discussed in this paper.Â